Explaining the Dollar-Euro rate: Do stock market returns mater? - Bernd Kaltenhäuser (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
This paper investigates how US and European equity markets affected the US dollar-euro rate from the introduction of the euro through April 2001. More detailed the following questions are raised: First, do movements in the stock market help to explain movements in the exchange rate? Second, how large is the impact of stock market returns on the exchange rate? And third, does the exchange rate respond differently to different equity markets? The investigation was carried out using daily data within a vector-autoregression model (VAR). Surprisingly, positive returns on US equities as well as on European stock markets had a negative impact on the US dollar-euro rate. Quantitatively, the US dollar-euro rate seems to be more influenced by European stock markets compared to US stock markets. Further, there is evidence for a somewhat weaker impact of technology stock indices on the US dollar-euro rate compared with broader market indices. Finally, the long-term interest rate differential seems to contain more information about exchange rate movements than the shortterm interest rate differential.
urn:nbn:de:hebis:30-9831
Keywords: C32; F31; 330; Exchange Rates; Information Share